(untitled) (Research, Society and Development, 2020)
Introduction: In Brazil, 13% of the population is composed of people with upper than 60 years, and is estimated that this number will be 29,3% in 2050. Objective: The goal of the study was to determine the profile and correlation between the variables: brain activity, functional autonomy, and frailty of the elderly with different daily physical activity. Methodology: Were selected 60 elderly inserted on an active and healthy aging program, with different levels of daily physical activity, of both sex, age upper than 60 years, and physical and cognitive functions preserved. Were evaluated frailty, functional autonomy, and daily physical activities, besides brain activity through an electroencephalogram, using as reference the international system 10/20. Results: The results showed that the more active participants got better results in functional autonomy and frailty tests, and also had recorded more brain activity in areas related to executive functions. Conclusion: The more active participants got better punctuations in functional autonomy and frailty tests, besides also got a higher brain activity. However, although the relationship found to have a background in the scientific literature, only the correlation between the frailty and functional autonomy scores was statistically significant.